Horizontal kinetic energy analysis of tropical transition simulations with the WRF and HARMONIE‐AROME models - Calvo Sancho, Carlos; Bolgiani, Pedro; Subias, Álvaro; Sastre Marugan, Maríano; González Alemán, Juan Jesús; Martín Pérez, María Luisa (Quarterly Journal of the Royal Meteorological Society, 2023)
Producción Científica Four tropical transition (TT) events in the North Atlantic basin are simulated with the Weather Research and Forecasting (WRF) and the HARMONIE-AROME (HAR) models to study the main features of the horizontal kinetic energy (HKE) spectra of these kinds of high-energetic atmospheric system. Though most of the times similar results are obtained with both models, HAR shows a more intense filtering and numerical dissipation, whereas WRF tends to represent overenergized spectra in the synoptic scale and especially at smaller wavelengths. Predictability is dissimilar for the four TTs studied due to the different spectral curve slope obtained for each case, ranging from unlimited to very poor predictability at synoptic scale. Additionally, an increased HKE is presented in the middle–upper troposphere spectra. A deep analysis of the different terms involved in the equation of the spectral energy budget is presented through a detailed study of one of these TTs. The role of all of them is studied, connecting the energy spectra and the meteorological processes involved. The energy budget terms related to the nonlinear spectral transfer, the three-dimensional divergence, and diabatic process tendencies are identified as the key ones, whereas the potential and kinetic conversion terms and the vertical flux HKE and pressure divergence terms play a secondary role on modulating the spectrum behaviour. The major energetic contributions are found at the synoptic scale, but results show that a two-dimensional energy cascade does not fully capture the whole spectrum of a TT. The role of convection, latent heat release, and moist convection outbursts is sketched and a link within different vertical levels is found. Results show that a high-energetic system, such as a TT, can effectively alter the atmospheric energy behaviour. Ministerio de Ciencia e Innovación, (Grant/Award Numbers:PID2019-105306RB-I00, PRE2020-092343) IBERCANES (project PID2019-105306RB-I00/AEI/10.13039/501100011033)